2021
DOI: 10.1155/2021/9925561
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Alleviates Cerebral Ischemia‐Reperfusion Injury through NLRP3 Inflammasome‐Mediated Pyroptosis Inhibition via Activating Nrf2

Abstract: As one of the fundamental components of Astragalus membranaceus, astragaloside IV (AST IV) exerts protective effects against cerebral ischemia-reperfusion injury (CIRI). Nevertheless, the underlying mechanisms have not yet been conclusively elucidated. To do so, here, we report on the regulatory effects of Nrf2 on NLRP3 inflammasome-mediated pyroptosis. CIRI was induced by middle cerebral artery occlusion-reperfusion (MCAO/R) in Sprague Dawley rats and modeled by oxygen and glucose deprivation/reoxygenation (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 38 publications
(48 reference statements)
4
20
0
Order By: Relevance
“…Further, a signi cant improvement was obtained by inhibiting Caspase-1 in ischemia-associated BBB permeability and integrity via inhibiting pyroptosis [31]. What's more, astragaloside IV alleviated CIRI through inhibiting NLRP3 in ammasome-mediated pyroptosis in MCAO/R rats and in OGD/R bEnd3 cells, further supporting inhibiting pyroptosis as a therapeutic strategy for CIRI [32]. The current study con rmed this as well.…”
Section: Discussionsupporting
confidence: 79%
“…Further, a signi cant improvement was obtained by inhibiting Caspase-1 in ischemia-associated BBB permeability and integrity via inhibiting pyroptosis [31]. What's more, astragaloside IV alleviated CIRI through inhibiting NLRP3 in ammasome-mediated pyroptosis in MCAO/R rats and in OGD/R bEnd3 cells, further supporting inhibiting pyroptosis as a therapeutic strategy for CIRI [32]. The current study con rmed this as well.…”
Section: Discussionsupporting
confidence: 79%
“…Studies have found that AST IV treatment could obviously increase SOD and LDH activities; reduce the production of NOS, MDA, and NO; and downregulate the expression of inducible nitric oxide synthase (iNOS) mRNA to ameliorate the oxidative damage in rats with cerebral I/R injury [ 56 ]. What is more, it could alleviate cerebral I/R injury through inhibiting NLRP3 inflammasome-mediated pyroptosis via activating Nrf2 [ 57 ]. Meantime, AST IV-tetramethylpyrazine played a pivotal synergistic protective role against focal cerebral ischemic reperfusion damage in a rat experimental model, which could downregulate MDA content and iNOS activity, and upregulate SOD activity [ 58 ].…”
Section: Protective Effects Of Tcm and Its Constituent Compounds On I...mentioning
confidence: 99%
“…Luteolin, a flavone, exerted cerebroprotection after subarachnoid hemorrhage ( 136 ) and neuroprotection after spinal cord ischemia-reperfusion injury ( 137 ) by preventing activation of NLRP3 inflammasome via the Nrf2 pathway. Astragaloside IV, a saponin found in Astragalus membranaceus , was found beneficial against cerebral ischemia-reperfusion injury ( 138 ), motor deficits, and dopaminergic neuron degeneration in a MPTP PD mouse model ( 139 ) via NLRP3/Nrf2 pathway regulation. A meroterpene from the seeds of Psoralea corylifolia , or bakuchiol, displayed similar effects by ameliorating cerebral ischemia-reperfusion injury via NLRP3/Nrf2 pathway ( 140 ).…”
Section: Preclinical Experience With Nrf2 Inducers Against Nlrp3 Infl...mentioning
confidence: 99%